Dynamic X-ray imaging of the magnetosheath expected during a super storm - Gong, Yuqi; Sun, Tianran; Tang, Binbin; Guo, Yihong; Sembay, Steve; Wang, Chi (Frontiers in Astronomy and Space Sciences, 2025)
The Earth’s magnetosheath is a vital source region of soft X-ray emissions generated by the solar wind charge exchange (SWCX) mechanism in geospace. Soft X-ray imaging provides valuable insights into the overall morphology of the magnetosheath. Nevertheless, the dynamic variations in X-ray images during extreme space weather have not been comprehensively studied. Using a global magnetohydrodynamic code, we simulated the temporal variations of the magnetosphere on 10-11 May 2024, during the most intense geomagnetic storm of Solar Cycle 25. The X-ray images of the magnetosphere during the entire event are presented to assess the response of the magnetosphere to the impact of the coronal mass ejection (CME), with a particular focus on the periods of sudden solar wind number density increase, the southward turning of the interplanetary magnetic field (IMF), and an extreme solar wind condition. With the advent of the Solar Wind-Magnetosphere-Ionosphere Link Explorer (SMILE), a joint mission between ESA and CAS, investigations into the large-scale structure and dynamic evolution of magnetopause will be enabled via global X-ray imaging.